The Application of Alphabet Cards to Improve Beginning Reading Skills for First Grade Students at State Elementary School - Binda Nitasari; Uyun , Tasniatul; Ella James-Brabham; Abel Mugenda; Rakhmatul Ummah (Tinta Emas Publisher, 2024)
Early reading skills development in lower grades requires substantial teacher support. At this stage, students begin to recognize letters and syllables, making effective teaching crucial for mastering reading skills. This research addresses the challenge of low early reading skills among first-grade students at State Elementary School (SDN) 47 Kodo Kota Bima, as identified through previous assessments. The study aims to evaluate the effectiveness of Alphabet Card media in improving these early reading skills. Using a classroom action research (CAR) approach, the research employs the Kemmis and McTaggart model, with the researcher conducting the teaching and the teacher and colleagues observing. Subjects are first-grade students at SDN 47 Kodo Kota Bima, with a focus on their early reading skills. Data collection methods include observation, interviews, and tests, analyzed descriptively and presented in tables and graphs. Results show a notable improvement in early reading skills. In the first cycle, the average percentage of improvement was 66.7% (good category), which increased to 73.5% (good category) in the second cycle. These findings suggest that Alphabet Card media effectively enhances early reading skills in students. The study concludes that Alphabet Card media is a beneficial tool for improving early reading skills and can positively impact learning outcomes for first-grade students.